Playing in nursing care in pediatric oncology: an integrating review - Gabriele de Jesus Lima, Karine; de Jesus Oliveira Neves, Sabrina; de Oliveira Santos, Kamilla; Emanuelle Santos, Bruna; Katerine Godinho Gomes, Bruna; Aparecida Nery Rodrigues, Ludmilla; Fernandes do Prado, Patrícia; Pereira de Freitas, Warley (Revista Unimontes Científica, 2020)
O BRINCAR NO CUIDADO DE ENFERMAGEM EM ONCOLOGIA PEDIÁTRICA: UMA REVISÃO INTEGRATIVA Playing in nursing care in pediatric oncology: an integrating review Resumo: No âmbito da oncologia pediátrica, entende-se ser preciso incluir o brincar na assistência como um recurso para um cuidado de enfermagem integral e humanizado. O estudo teve como objetivo identificar, na literatura, as formas de utilização do brincar no cuidado de enfermagem em oncologia pediátrica. Trata-se de um estudo de revisão integrativa da literatura com artigos científicos publicados no período de 2012 a 2017, cujas pesquisas fossem nacionais e estivessem disponíveis na íntegra na plataforma de periódicos da Biblioteca Virtual em Saúde. Dos 21 estudos identificados, 11 foram incluídos nesta revisão. Os principais resultados apontaram algumas formas de utilização do brincar pela equipe de enfermagem atuante em oncologia pediátrica, destacando-se a contação de estórias, a brinquedoteca e o brinquedo terapêutico. Conclui-se que o brincar deve estar presente no cuidado, sempre que possível, para propiciar uma assistência integral e humanizada a essas crianças e a diminuição de traumas e prejuízos no seu desenvolvimento. Abstract: In the context of pediatric oncology, it is understood that it is necessary to include play in care as a resource for comprehensive and humanized nursing care. The aim of this study was to identify the ways in which play in nursing care in pediatric oncology can be used. This is an integrative review of the literature with scientific articles published in the period 2012 to 2017, whose research was national and was available in full in the periodical platform of the Virtual Health Library (VHL). Of the 21 studies identified, 11 were included in this review. The main results point to some forms of use of play by the nursing team active in pediatric oncology, highlighting the story telling, toy library and therapeutic toy. It is concluded that playing should be present in the care, as far as possible to provide comprehensive and humanized care to these children and the reduction of trauma and developmental harm. Abstract: In the context of pediatric oncology, it is understood that it is necessary to include play in care as a resource for comprehensive and humanized nursing care. The aim of this study was to identify the ways in which play in nursing care in pediatric oncology can be used. This is an integrative review of the literature with scientific articles published in the period 2012 to 2017, whose research was national and was available in full in the periodical platform of the Virtual Health Library (VHL). Of the 21 studies identified, 11 were included in this review. The main results point to some forms of use of play by the nursing team active in pediatric oncology, highlighting the story telling, toy library and therapeutic toy. It is concluded that playing should be present in the care, as far as possible to provide comprehensive and humanized care to these children and the reduction of trauma and developmental harm.